PERAN PRESS RELEASE SEBAGAI BENTUK PENYEBARAN INFORMASI PUBLIK DI BAGIAN HUMAS PEMERINTAH KOTA GORONTALO - admin, admin; Tolapa, Minarni (Al Qisthi: Jurnal Sosial dan Politik, 2018)
Press Release is one of the Public Relations activities in conducting publications related to informations regarding events that occur in an institution or organization. This study aims to analyze the role of press release as a form of public information dissemination in the Public Relations Department of the Gorontalo City Government. This research was conducted at the Gorontalo City Government Institution. The method used in this study is a qualitative descriptive research method. The research informants were obtained purposively. Data collection is done through observation and in-depth interviews with informants, document and literature studies. Data analysis techniques use Miles and Huberman data analysis technique which consist of data collection, data reduction, data display and conclusion/drawing verification. The research results that the Press Release has an important role as supporting Public Relations publications activities of the Gorontalo City Government. Press Release as a form of disseminating public information plays a role that is quite effective and efficient in conveying accurate information to the public.